Long noncoding RNA XXYLT1-AS2 regulates proliferation and adhesion by targeting the RNA binding protein FUS in HUVEC. (April 2020) - Wang, Qi; Yang, Yanyan; Fu, Xiuxiu; Wang, Zhibin; Liu, Yan; Li, Min; Zhang, Yinfeng; Li, Yonghong; Li, Pei-feng; Yu, Tao; Chu, Xian-ming
Abstract: Background and aims: The endothelium is crucially involved in the pathogenesis of atherosclerosis according to accumulating evidence. Moreover, recent studies have showed that lncRNAs could serve as biomarkers of cardiovascular diseases, in particular atherosclerosis. However, the underlying mechanism of endothelial dysfunction involving lncRNAs in atherosclerosis remains unknown. This study investigated the mechanism of lncRNA XXYLT1-AS2 in endothelial dysfunction in atherosclerosis. Methods: The levels of lncRNA XXYLT1-AS2, FUS, VCAM-1, MCP-1, p-AKT, and p-P65 were measured in arteries and HUVEC cell lines via quantitative real-time PCR or Western blot. FISH assay demonstrated that XXYLT1-AS2 and FUS are localized in the nucleus. HUVECs were transfected with si- XXYLT1-AS2 or XXYLT1-AS2 to further assess cell proliferation, migration, and adhesion. Furthermore, bioinformatics analysis, RNA immunoprecipitation and immunofluorescence were performed to investigate the target genes of XXYLT1-AS2 and possible signal pathways. Results: Overexpression of XXYLT1-AS2 inhibited cell proliferation and migration, reduced the expression of adhesion molecules (VCAM-1) and chemoattractant proteins (MCP-1), and restrained monocyte adhesion to endothelial cells. Mechanistic investigations indicated that XXYLT1-AS2 directly interacts with the target gene FUS/cyclin D1 and modulates the proliferation and migration of endothelial cells (ECs). Moreover, XXYLT1-AS2 exerts a protective role against the inflammatory response in atherosclerosis by blocking NF-κB activity. Clinically, the involvement of XXYLT1-AS2 /FUS was also observed in human arteries and the results were consistent with the in vitro analysis. Conclusions: Our study identified a novel long non-coding RNA ( XXYLT1-AS2 ) and suggests that it might act as an underlying therapeutic target in atherosclerosis-related diseases by regulating ECs functions. Graphical abstract: Image 1 Highlights: LncRNA XXYLT1-AS2 modulates endothelial dysfunction to serve as a critical repressor of atherosclerosis. LncRNA XXYLT1-AS2 upregulated FUS expression, thereby inhibiting HUVEC proliferation and migration via repressing cyclin D1. LncRNA XXYLT1-AS2 negatively regulated monocyte adhesion and the level of VCAM-1 and MCP-1 by targeting NF-κB pathway.